160k views
2 votes
Simply
6(2x + 1) = 2(5x + 2)
18

User Tong Xu
by
5.1k points

1 Answer

4 votes

Answer:

x=−1

Explanation:

Step 1: Simplify both sides of the equation.

6(2x+1)=2(5x+2)

(6)(2x)+(6)(1)=(2)(5x)+(2)(2)(Distribute)

12x+6=10x+4

Step 2: Subtract 10x from both sides.

12x+6−10x=10x+4−10x

2x+6=4

Step 3: Subtract 6 from both sides.

2x+6−6=4−6

2x=−2

Step 4: Divide both sides by 2.

x=−1

User Benoit Thiery
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.